Does diet form (pelleted vs meal) affect optimum particle size of corn for finishing pigs? - Wondra, K.J.; Kennedy, G.A.; Hines, Robert H.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and sixty pigs, with an average initial wt of 121 lb, were used in an experiment to determine the effects of diet form and particle size on growth performance and nutrient digestibility. The pigs were fed corn-soybean meal-based diets with the corn milled to particle sizes of 1,000, 800, 600, or 400 p,m. The diets were fed in meal and pellet forms. In general, reducing particle size increased electrical energy required for milling and decreased production rate. Milling to 400 p,m, as opposed to 600 JLm, required twice as much electrical energy and reduced production rate by 50%. Reducing particle size of the corn from 1,000 to 400 p,m resulted in a 4% increase in DE of the diets and 6% decrease in ADFl. The net result was similar DE intakes, with 22% less daily fecal excretion of DM, 25% less daily fecal excretion of N, and 7% greater efficiency of gain when particle size was reduced from 1,000 to 400 /Lm. Pelleting the diets resulted in 3% greater ADG and 6% greater efficiency of gain. Also, pelleting increased digestibilities of DM, N, and GE by 5 to 7 %. Stomach keratinization and lesions increased with reduced particle size and pelleting, but performance was not affected. In conclusion, particle size reduction and pelleting improved efficiency of gain and decreased daily excretion of DM and N in the feces, with some increase in ADG because of pelleting.
Keywords: Swine; Process; Particle size; Pellet; Performance; Stomach ulcer; G-F